Complexation of trivalent metal cations (Al3+, Ga3+, In3+, La3+, Lu3+) to cucurbiturils: a DFT/SMD evaluation of the key factors governing the host–guest recognition. Issue 10 (1st March 2022) - Koleva, Iskra Z.; Dobrev, Stefan; Kircheva, Nikoleta; Dasheva, Lyubima; Nikolova, Valya; Angelova, Silvia; Dudev, Todor
Abstract : DFT calculations are employed to investigate the interactions of a series of trivalent metal cations (Al 3+, Ga 3+, In 3+, La 3+, Lu 3+ ) to cucurbit[ n ]urils and to evaluate the main factors controlling the host–guest complexation. Abstract : Cucurbiturils (CBs), the pumpkin-shaped macrocycles, are suitable hosts for an array of neutral and cationic species. A plethora of host–guest complexes between CBs and a variety of guest molecules has been studied. However, much remains unknown, even in the complexation of very simple guests such as metal cations. In the computational study herein, DFT molecular modeling has been employed to investigate the interactions of a series of trivalent metal cations (Al 3+, Ga 3+, In 3+, La 3+, Lu 3+ ) to cucurbit[ n ]urils and to evaluate the main factors controlling the host–guest complexation. The thermodynamic descriptors (Gibbs energies in the gas phase and in a water environment) of the corresponding complexation reactions have been estimated. This research is a logical continuation of an earlier study on the interaction between CB[ n ]s and a series of biologically essential mono- and divalent metal cations (Na + /K + and Mg 2+ /Ca 2+, respectively).